2021
DOI: 10.1186/s13068-021-01984-0
|View full text |Cite
|
Sign up to set email alerts
|

Two Fusarium copper radical oxidases with high activity on aryl alcohols

Abstract: Background Biomass valorization has been suggested as a sustainable alternative to petroleum-based energy and commodities. In this context, the copper radical oxidases (CROs) from Auxiliary Activity Family 5/Subfamily 2 (AA5_2) are attractive biocatalysts for the selective oxidation of primary alcohols to aldehydes. Originally defined by the archetypal galactose 6-oxidase from Fusarium graminearum, fungal AA5_2 members have recently been shown to comprise a wide range of specificities for aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 94 publications
(185 reference statements)
1
38
0
1
Order By: Relevance
“…32 Taking advantage of recombinant enzyme production pipelines, a large diversity of AA5_2 enzymes has been recently characterized. 9,10,33–36…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Taking advantage of recombinant enzyme production pipelines, a large diversity of AA5_2 enzymes has been recently characterized. 9,10,33–36…”
Section: Introductionmentioning
confidence: 99%
“…32 Taking advantage of recombinant enzyme production pipelines, a large diversity of AA5_2 enzymes has been recently characterized. 9,10,[33][34][35][36] GalOx activity has historically been measured by indirect, spectrophotometric methods that rely on quantifying the coproduct H 2 O 2 using a coupled horseradish peroxidase (HRP)/ 2,2 0 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assay. 37 Despite widespread use, such assays have certain limitations due to the cross-reactivity of H 2 O 2 or the instability of the reporter molecule (ABTS cation radical).…”
Section: Introductionmentioning
confidence: 99%
“…HMF, via its oxidized derivatives, is a biomass-derived feedstock of particular contemporary interest and an exemplar aryl alcohol substrate of AA5 CROs. We previously showed that the dialdehyde DFF is the sole product of HMF oxidation by wild-type Cgr AAO . As the Cgr AAO-Δloop variant gained the ability to oxidize DFF at the expense of HMF activity (Table ), product analysis by NMR experiments was performed on these two substrates.…”
Section: Resultsmentioning
confidence: 99%
“…1.1.3.13), and aryl alcohol oxidases (AAO, E.C. 1.1.3.7), , which convert the primary alcohol of their respective substrates to the corresponding aldehyde. Catalysis in AA5 members is mediated by a mononuclear copper center, which is coordinated by a unique cross-linked tyrosine–cysteine radical cofactor; molecular oxygen (O 2 ) serves as the final electron acceptor to generate hydrogen peroxide (H 2 O 2 ) as a co-product. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation